Аналіз та вибір об’єктів-представників багатоповерхового будівництва - Черненко, К. В.; Білик, А. С.; Гавалешко, В. М. (Ways to Improve Construction Efficiency, 2014)
The methodology of multi-storey buildings representative objects selection is investigating to determine rational solutions for the further development of a more efficient way of their construction.